Design and Development of WEB Payroll Information System at PT Cipta Guna Lestari - Julian, Felix; Widjaja, Prya Artha (PT FORMOSA CENDEKIA GLOBAL, 2024)
The digital era has brought significant changes to various fields, including business. Technology, according to Gary J. Anglin (1991), is the application of science to solve problems systematically. One of its applications is a web-based payroll system, which increases the ease and accuracy of filling in salary data. However, concerns about information security still hamper its adoption in a number of companies. PT Cipta Guna Lestari, a trading company in Cilegon, needs this system to improve the accuracy and timeliness of salary payments, which affect employee performance and productivity. System testing showed positive results: users can manage data, process leave, print reports, and record absences with appropriate access. The implementation of this system is expected to increase efficiency, reduce the risk of delays, and simplify the payroll process at PT Cipta Guna Lestari.